Analisis Surat-Surat RA. Kartini Atas Pemikiran Pendidikan Perempuan dan Relevansinya dengan Pendidikan Islam dalam Keluarga - Nurochman, Nurochman; Ali, Mudzakkir (Universitas Wahid Hasyim Semarang, 2023)
The purpose of this research is, firstly, to find out how the education of indigenous women RA. Kartini. Second, to find out the relevance of RA Kartini's indigenous women's educational thinking to Islamic Education. In this study using the library research method (Library Research) with the main source being a collection of letters